Aggregate versus individual-level sexual behavior assessment: how much detail is needed to accurately estimate HIV/STI risk? - Pinkerton, Steven D; Galletly, Carol L; McAuliffe, Timothy L; Difranceisco, Wayne; Raymond, H Fisher; Chesson, Harrell W (Evaluation review, 2010)
The sexual behaviors of HIV/sexually transmitted infection (STI) prevention intervention participants can be assessed on a partner-by-partner basis: in aggregate (i.e., total numbers of sex acts, collapsed across partners) or using a combination of these two methods (e.g., assessing five partners in detail and any remaining partners in aggregate). There is a natural trade-off between the level of sexual behavior detail and the precision of HIV/STI acquisition risk estimates. The results of this study indicate that relatively simple aggregate data collection techniques suffice to adequately estimate HIV risk. For highly infectious STIs, in contrast, accurate STI risk assessment requires more intensive partner-by-partner methods.
Keywords: Algorithms; Female; Health Promotion; HIV Infections; Humans; Male; Models, Theoretical; Prevalence; Public Health; Risk Assessment; Risk Factors; Risk-Taking; Sexually Transmitted Diseases; Social Marketing; United States; Unsafe Sex